Reduction in Surgical Wound Infection Rates Associated with Reporting Data to Surgeons. (1994) - Taylor, GD; Buchanan-Chell, M; Kirkland, T; McKenzie, M; Sutherland, B; Wiens, R
Abstract : Several studies have shown that wound infection (surgical site infection [ ssi ]) rates fall when surgeons are provided with data on their performance. Since 1987, the authors have been performing concurrent surveillance of surgical patients and confidentially reporting surgeon-specific ssi rates to individual surgeons and their clinical directors, and providing surgeons with the mean rates of their peers. The program has been gradually refined and expanded. Data are now collected on wound infection risk and report risk adjusted rates compared with the mean for hospitals in the United States National Nosocomial Infections Surveillance (nnis ) data bank. Since inception through to December 1993, ssi rates have fallen 68% in clean contaminated general surgery cases (relative risk [rr ] 0.36, 95% ci 0.2 to 0.6, P=0.0001), 64% in clean plastic surgery cases (rr 0.35, 95% ci 0.06 to 1.8), 72% in caesarean section cases (rr 0.23, 95% ci 0.03 to 1.96) and 42% in clean cardiovascular surgery cases (rr 0.59, 95% ci 0.34 to 1.0). In clean orthopedic surgery the ssi rate remained stable from 1987 through 1992. In 1993 a marked increase was experienced. Reasons for this are being explored. Overall there was a 32% decrease in ssi rate between the index year and 1993 or, in percentage terms, 2.8% to 1.9% (rr 0.65, 95% ci 0.51 to 0.86, P=0.002). ssi surveillance should become standard in Canadian hospitals interested in improving the quality of surgical care and reducing the clinical impact and cost associated with nosocomial infection.